QISHASH SEBAGAI ETIKA KEMANUSIAAN: PEMIKIRAN AL-QURṬUBĪ DAN RELEVANSINYA BAGI KEPATUHAN SDM DI INDONESIA - Syuhada, Wira; Yaqin, Hamdan Ainul; Edy, Tjatur Sapto; Setiansah, Restu Haji (Tajdid: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2026)
This study examines the thought of Imam al-Qurṭubī on the law of qishash as elaborated in Tafsīr al-Jāmiʿ li Aḥkām al-Qurʾān, focusing on Q.S. Al-Baqarah: 178-179, and integrates its universal values into modern Human Resource Management (HRM) practice in Indonesia. Using a qualitative library research approach, the study reveals that al-Qurṭubī interprets qishash as a mechanism of justice aimed at preserving life (ḥifẓ al-nafs) and social stability. Values of justice, equality, and deterrence (zawājir) contained in qishash are significantly relevant for disciplinary policy formulation, proportional sanction systems, and a justice-based compliance culture in HRM. The article concludes that the spirit of Islamic law as explained by al-Qurṭubī provides a strong ethical and philosophical foundation for fair and sustainable HRM practice in Indonesia